Separation and quantification of 9-(alkylthio)acridines by capillary micellar electrokinetic chromatography and capillary liquid chromatography - Nejmanová, Jana; Coufal, Pavel; Bosáková, Zuzana; Sobotníková, Jana; Tesařová, Eva (Journal of separation science, 2007)
Various thioacridine derivatives are potential chemotherapeutics against various diseases which are intensively synthesized, characterized, and investigated by many research groups. Efficient, fast, and reliable separation and quantification methods for their analysis are still to be developed. MEKC and capillary LC (CLC) were applied for the separation and quantification of five highly hydrophobic, weakly basic, and structurally similar 9-(alkylthio)acridines. Since the common anionic and cationic surfactants failed to separate the strongly hydrophobic thioacridines by MEKC, sodium cholate was used in an alkaline BGE and successfully employed for their fast separation. In CLC, the weakly basic nature of the thioacridines necessitated use of LiChrosorb RP-select B sorbent as the stationary phase, which combined with a very simple mobile phase methanol/water yielded an efficient chromatographic separation system. Both, the MEKC and CLC optimized separation methods were then applied to quantify the thioacridines within a concentration range of 1.0 x 10(-5)-1.0 x 10(-3) mol/L and the obtained experimental results were critically compared. In practical terms, the MEKC analytical method can quantify the analytes much faster but with a lower reliability while the CLC method performs slower analysis with a higher repeatability of the experimental results.
Keywords: financování organizované; Sodium Cholate; cholát sodný; chromatografie micelární elektrokinetická kapilární; Molecular Structure; Financing, Organized; molekulární struktura; kalibrace; Acridines; Calibration; pufry; Buffers; Chromatography, Liquid; močovina; Urea; chromatografie kapalinová; akridiny; Chromatography, Micellar Electrokinetic Capillary